Private Brands and Store Loyalty: An Empirical Study in Noida - Singhi, Rushina; Kawale, Dewyani (Indian Journal of Marketing, 2010)
Private labels have come a long way over the last three decades. They started with retailers wanting to offer cheaper substitutes. This was for two reasons. One, having a private label meant that retailers could negotiate a better margin from the manufacturer. And the other, when they had private labels, they had a differentiator. The biggest change in the last decade or so has been the entry of premium private labels. They are no longer saying "buy us because we are cheap", instead today; they are saying "buy us because we are the best". By offering high quality products, many private labels have started charging more than regular manufacturers. Retailers are looking at private labels or store labels as one of the option to drive the customers to their stores. The emergence of organized retailing in India has made Private Labels a reality. It is now well within the reckoning of the consumer, retailers and brand owners. A Private Label is not merely a product with the store/retailer’s name on it. It takes more to qualify as a Private Label. The consumer must see the Private Label product as distinct from being just a ’product in a pack’. There must be a clear perception that ’it is produced by this store’.